HUBUNGAN PERSEPSI SISWA TENTANG SIKAP GURU DENGAN MINAT BELAJAR SISWA SELAMA PEMBELAJARAN DARING - Deny K, Paulinus; Lestiawati, Endang; Aini, Rozian Husnatul (Coping: Community of Publishing in Nursing; Vol 10 No 3 (2022): Juni 2022, 2022)
Students' low interest in learning is influenced by several factors, both internal and external factors. The attitude of the teacher in teaching is one of the external factors that influence students' interest in learning. Teachers in the classroom must always pay attention to things that can foster student interest in learning, especially pay attention to the problem of attitude, because the figure of a teacher will not be separated from the views and assessments of students. The purpose of this study was to determine the relationship between students' perceptions of teacher attitudes and student interest in learning in grades IV-V during online learning at SDN 1 Rumbuk Timur, East Lombok. This type of research is correlation analytic with cross sectional design. The research subjects were students in grades IV-V. The sample in this study amounted to 73 students. The sampling technique used was total sampling . The research instrument used a questionnaire on student perceptions about teacher attitudes and learning interest that had been carried out by expert judgment with a value of 0.85. Bivariate analysis using chi-square test. Student perceptions in the good category were 48 people (65,8%), interest in learning in the good category were 47 people (64,4%). The results of the bivariate analysis obtained a p-value of 0,000 (<0,05). Students' perceptions of teacher attitudes are one of the factors related to student interest in learning in grades IV-V at SDN 1 Rumbuk Timur, East Lombok.